Study of a Jacobian-free approach in the simulation of compressible fluid flows in porous media using a derivative-free spectral method. (March 2015) - Henderson, Nélio; Simão, Gisiane; Sacco, Wagner F.
Highlights: We employ the DFSANE algorithm in the simulation of miscible flows in porous media. We report results and comparisons with a Jacobian-free inexact Newton method. The DFSANE was able to simulate miscible processes using the lowest CPU time. Abstract: The development of Jacobian-free software for solving problems formulated by nonlinear partial differential equations is of increasing interest to simulate practical engineering processes. For the first time, this work uses the so-called derivative-free spectral algorithm for nonlinear equations in the simulation of flows in porous media. The model considered here is the one employed to describe the displacement of miscible compressible fluid in porous media with point sources and sinks, where the density of the fluid mixture varies exponentially with the pressure. This spectral algorithm is a modern method for solving large-scale nonlinear systems, which does not use any explicit information associated with the Jacobin matrix of the considered system, being a Jacobian-free approach. Two dimensional problems are presented, along with numerical results comparing the spectral algorithm to a well-developed Jacobian-free inexact Newton method. The results of this paper show that this modern spectral algorithm is a reliable and efficient method for simulation of compressible flows in porous media.